The Investigation of Nationalism Values Through PKn Learning for Class V Students at UPT SPF SDN 106803 Pematang Johar School Year 2022/2023 - Hafizah, Nurul (Berpusi Publishing, 2023)
This research aims to analyze the implementation of instilling nationalist values ​​through Civics learning in class V students at UPT SPF SDN 106803 Pematang Johar. This research is research that uses descriptive research methods with a qualitative approach used to describe and answer problems in detail. Data collection techniques include observation, interviews and documentation. The results of this study are: 1) UPT SPF SDN 106803 Pematang Johar has instilled nationalist values ​​through all learning activities, especially in Civics learning and non-academic activities through programs set by the school and extracurricular activities; 2) the obstacles experienced during the process of instilling nationalist values ​​are due to environmental factors which have quite a big influence on the formation of student behavior, lack of knowledge of nationalist values, as well as the influence of globalization which is not addressed properly; 3) Efforts that can be made to overcome these obstacles are by carrying out established school programs through religious activities, carrying out extracurricular scout activities, mutual cooperation activities, literacy activities, and visiting museums through study tour activities. lack of knowledge of nationalist values, as well as the influence of globalization which is not addressed properly; 3) Efforts that can be made to overcome these obstacles are by carrying out established school programs through religious activities, carrying out extracurricular scout activities, mutual cooperation activities, literacy activities, and visiting museums through study tour activities. lack of knowledge of nationalist values, as well as the influence of globalization which is not addressed properly; 3) Efforts that can be made to overcome these obstacles are by carrying out established school programs through religious activities, carrying out extracurricular scout activities, mutual cooperation activities, literacy activities, and visiting museums through study tour activities.